Renal Medullary Carcinoma With Metastasis to the Temporal Fossa and Orbit. Issue 6 (November 2019) - Chumdermpadetsuk, Ritah; Tooley, Andrea A.; Godfrey, Kyle J.; Krawitz, Brian; Feldstein, Neil; Kazim, Michael
Abstract : A 22-year-old Hispanic man with sickle cell trait presented with blurred vision, double vision, and pain with OD movement. MRI demonstrated an extra-axial mass centered around the temporal bone with extension into the middle cranial fossa and lateral aspect of the extra-conal right orbit, and mass effect on the lateral rectus muscle. Biopsy of the lesion was consistent with renal medullary carcinoma. CT chest/abdomen/pelvis confirmed a primary tumor in the right kidney. No additional metastases were found. Renal medullary carcinoma is a rare, highly aggressive malignancy, which almost exclusively affects young men of African descent with sickle cell trait or sickle cell disease. The authors present the second confirmed case of renal medullary carcinoma metastatic to the orbit, with ocular symptoms prior the typical presenting symptoms of flank pain and hematuria. Renal medullary carcinoma is a highly aggressive malignancy, most commonly seen in African American patients with sickle cell disease. Involvement of the orbit is rare and visual symptoms may precede systemic diagnosis.